2020
DOI: 10.1002/spe.2933
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging machine learning for software redocumentation—A comprehensive comparison of methods in practice

Abstract: Source code comments contain key information about the underlying software system. Many redocumentation approaches, however, cannot exploit this valuable source of information. This is mainly due to the fact that not all comments have the same goals and target audience and can therefore only be used selectively for redocumentation. Performing a required classification manually, for example, in the form of heuristics, is usually time‐consuming and error‐prone and strongly dependent on programming languages and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…AI is an area of computer science, and it is concerned with the process of analyzing large amounts of data. Machine learning 52 is an application or subset of AI that enables our algorithms to automatically develop and adapt expertise without even being overtly programmed. Keeping all this in observance, a hybrid classification approach is proposed in this section, where the integration of machine learning and heuristic analysis is exemplified.…”
Section: Proposed Methodologymentioning
confidence: 99%
“…AI is an area of computer science, and it is concerned with the process of analyzing large amounts of data. Machine learning 52 is an application or subset of AI that enables our algorithms to automatically develop and adapt expertise without even being overtly programmed. Keeping all this in observance, a hybrid classification approach is proposed in this section, where the integration of machine learning and heuristic analysis is exemplified.…”
Section: Proposed Methodologymentioning
confidence: 99%
“…It is crucial to assess whether these stakeholders understand the query responses provided by the trained model. User guidelines around functions, business rules and domain concepts related to ML models can potentially be generated automatically [102] to provide end-users with explanations for the functionalities, operational mechanisms and restrictions that drive an ML solution.…”
Section: Deploymentmentioning
confidence: 99%
“…Chittimalli et al 30 reported on a more ambitious goal: a language‐independent framework to extract the rules, 31 to create new ones, to verify them using the logs, and to analyze them. Geist et al 32 were able to extract business rules from source code statements with the aim of generating documentation for software tools automatically. Saruwatari et al, 33 highlighted the difficulty to extract business rules from general purpose programming languages and suggested to analyze the execution logs instead.…”
Section: Related Workmentioning
confidence: 99%